Polyoxometallates for use at elevated temperatures and pressures - ANDREW MARTIN CREETH; MATTHEW ALEXANDER HERBERT; DAVID ROCHESTER (2014)
A redox fuel cell 1 is disclosed comprising an anode and a cathode 3 separated by an ion selective polymer electrolyte membrane 2; means for supplying a fuel to the anode and an oxidant to the cathode; a non-volatile catholyte solution comprising a polyoxometallate redox couple being at least partially reduced at the cathode, and at least partially re-generated by reaction with the oxidant in a regeneration zone, the catholyte solution further comprising at least one vanadium species that results from the speciation of the polyoxometallate Xa[ZbMcOd] at an elevated temperature and/or pressure, wherein X is selected from hydrogen, alkali metals, alkaline earth metals, ammonium, transition metal ions and combinations of two or more thereof; Z is selected from B, P, S, As, Si, Ge, Ni, Rh, Sn, Al, Cu, I, Br, F, Fe, Co, Cr, Zn, H2, Ta, Mn and Se and combinations of two or more thereof; M comprises vanadium and optionally one or more of Mo, W, Nb, Ta, Mn, Fe, Co, Cr, Ni, Zn Rh, Ru, Tl, Al, Ga, In and other metals; b is from 0 to 20; c is from 1 to 40; d is from 1 to 180; X includes a non-hydrogen cation and the molar ratio of the non-hydrogen cation to vanadium is more than 0 and less than 2. The preferred polyoxometallates are KH6PV4Mo8O40, NaH6PV4Mo8O40 or K0.5H9.5P2V4Mo8O44.